(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: The most common contemporary strategy to diagnose chronic hepatitis C virus (HCV) infection consists of initial screening with an HCV enzyme immunoassay (EIA) antibody test followed by supplemental testing of positive screening tests with a quantitative HCV RNA assay to confirm the positive EIA and to determine whether they have active or resolved hepatitis C infection. Objectives: To detect and quantify HCV-RNA by real-time polymerase chain reaction (real-time PCR) among anti-HCV positive patients and to identify the socio demographic factors among these patients. Materials and Methods: This was a descriptive type of cross-sectional study which was conducted in Combined Military Hospital and Armed Forces Institute of Pathology, Dhaka cantonment. A total of 108 anti-HCV positive patients by enzyme-linked immunosorbent assay (ELISA), who were clinically suspected and advised for anti-HCV test, were selected randomly for the study and subjected to do HCV-RNA analysis during the period of October 2016 to September 2017. Results: Out of 108 anti-HCV positive patients by ELISA, HCV-RNA was detected in 72 (66.7%) cases with mean value of HCV RNA quantification was 2013323.95±2695207.41 (IU/ ml). Majority of anti-HCV positive patients (29.6%) belonged to 51-60 years age group with male predominance (58.33%). It was observed that 43.52% patients came from middle income group family, 31.48% came from poor and 25.0% came from high income group family. Risk factor for HCV infected population was found maximum in dialysis patients (47.37%), followed by blood transfusion (13.89%), Injecting drug User (IDUs) (12.04%), surgery & intervention (9.26%) and sexual transmission (1.85%). Mean alanine aminotransferase (ALT) was found 67.30±44.99 U/L among HCV-RNA detected patients (p< 0.05). Conclusion: The quantification of HCV RNA by RT-PCR will be helpful to rationalize the treatment, enhance antiviral responses and mitigate mortalities of HCV infected patients. Journal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 84-86